Pengaruh Social Media Marketing Pada Akun Tiktok @boboholokal Terhadap Brand Engagement Disney+ Hotstar - Hanifa, Hazna Mutia; Arifputri, Aiza Nabilla (eProceedings of Management, 2024)
Korean Dramas are very popular in Indonesia, from the storyline, characters, soundtrack, and culture, to becomingpopular shows in various countries. According to Databoks in August 2022, a digital survey by Telkomsel showedthat Disney+ Hotstar was the most used streaming service in Indonesia. Disney+ Hotstar is a streaming service thatutilizes TikTok as a tool for social media marketing activities (Yadav and Rahman, 2018). One of the accounts thatmarkets through TikTok is Alex Simanjuntak, a content creator, owner of the TikTok account @boboholokal, whichfocuses on Korean dramas. This study aims to examine the extent of the influence of social media marketing on theTikTok account @boboholokal, with 2 million followers as of January 8, 2024, on the brand engagement (Hollebeek,2014) of Disney+ Hotstar. The research method used is descriptive quantitative with non-probability samplingtechniques to 400 respondents. The research results indicate that variable X, which is social media marketing, has asignificant positive impact on variable Y, which is brand engagement. The social media marketing variable on theTikTok account @boboholokal has a 54.5% influence on the brand engagement of Disney+ Hotstar, while theremaining 45.5% is due to factors not examined in this study. Keywords-brand engagement, disney+ hotstar, korean drama, social media marketing, tiktok.